TDIC’S IN CHEMISTRY TEACHING AS A PROPOSAL OF INCLUSION FOR AUTISTIC STUDENTS AND WITH TDAH - Joyciele Cosmo de Araújo, Maria; da Silva Lacerda Junior, Orivaldo (Journal of Interdisciplinary Debates, 2022)
Inclusive education, although it has been the subject of important questions for educational development, is a teaching modality that serves an audience with some type of special needs and that these deserve greater attention in the practice of teaching Chemistry. With technological advances, it is feasible to insert this resource in Chemistry Teaching as a support for teachers in the process of including students with autism and TDAH, being a promising resource for the performance of teaching and learning. Conducted through a bibliographic and field survey in order to collect information on the subject, TDIC’s in Chemistry Teaching as a proposal for the inclusion of autistic and TDAH students, in which it aimed to analyze the importance of technological tools both to help teachers in inclusive methodological practices such as promoting knowledge on the part of students, especially those with disabilities, enrolled in high school, providing relevant and more attractive classes. It is also based on the analysis of a questionnaire in order to evaluate the qualification of initial training of teachers for the inclusive process and how to use methodologies adapted to technological tools in Chemistry Teaching. Thus, it concludes that the TDIC’s promote essential resources to help Chemistry teachers to develop an inclusive education, providing meaningful classes to students and guaranteeing the right of citizenship to all.